Pain Relief in labour: A randomized controlled trial comparing pentazocine with Tramadol - Kuti, O; Faponle, AF; Adeyemi, AB; Owolabi, AT (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To assess and compare the analgesic efficacy and side effects of Pentazocine and Tramadol. Method: This double blind randomised controlled trial was carried out at the labour ward of Wesley Guild Hospital Ilesa Nigeria. One hundred normal pregnant women in active labour at term were randomly assigned to receive either intramuscular Pentazocine 30mg or intramuscular tramadol 100mg, at request for analgesia. Analgesic efficacy was assessed by verbal scales of pain intensity and relief; maternal and neonatal side effects were determined. Results: At 60 minutes after drug administration 47.7% and 30.9% of women, in the pentazocine and tramadol group respectively, experienced moderate to good pain relief. Significantly more women in the pentazocine group (34.1%) than in the tramadol group(14.3%) rated their pain as mild (P < 0.05) sixty minutes after drug administration. Mean time to first subsequent request for analgesia was greater in the pentazocine group (181 minutes vs 113 minutes; P < 0.05). There was no significant differences between the drugs in maternal side effects, labour and neonatal outcomes. Conclusion: Pentazocine provides better pain relief than tramadol in labor. Key words: Labour pain, pentazocine, tramadol <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3126/njog.v3i1.1433 NJOG 2008 May-June; 3(1): 14 - 18